Understanding Conversational AI: Philosophy, Ethics, and Social Impact of Large Language Models - Thierry Poibeau (Ubiquity Press, 2025)
This book offers a critical and interdisciplinary exploration of large language models (LLMs), examining how they reshape our understanding of language, cognition, and society. Drawing on philosophy of language, linguistics, cognitive science, and AI ethics, it investigates how these models generate meaning, simulate reasoning, and perform tasks that once seemed uniquely human—from translation to moral judgment and literary creation. Rather than offering a purely technical account, the book interrogates the epistemic, ethical, and political dimensions of LLMs. It explores their limitations, their embedded biases, and their role in processes of automation, misinformation, and platform enclosure. At the same time, it reflects on how LLMs prompt us to revisit fundamental questions: What is understanding? What is creativity? How do we ascribe agency or trust in a world of synthetic language? Written for scholars, students, and curious readers across the humanities, social sciences, and computer science, this is both a philosophical inquiry and a practical guide to navigating the era of generative AI. It invites readers to think critically about the promises and perils of language technologies—and about the kind of future we are shaping with them.